Underwater sound in an urban estuarine river: Sound sources, soundscape contribution, and temporal variability - Marley, Sarah Anne; Erbe, Christine; Salgado Kent, Chandra (Australian Acoustical Society, 2016)
Human waterborne activities emit noise into the marine environment. This is of particular concern with regard to the potential impact on marine fauna such as cetaceans due to their acoustic specialisations. The Swan-Canning River system in Western Australia is home to a resident community of Indo-Pacific bottlenose dolphins (Tursiops aduncus), but is also a site regularly used for various human activities. As underwater noise levels increasingly become considered as an indicator of habitat quality, there is a need to characterise the soundscapes of such areas with regard to their cetacean fauna. This study aimed to provide a description of a site within the river system known as “The Narrows”. Acoustic data were collected over a six-week period with an autonomous underwater acoustic recorder. These data were analysed using a combination of weekly spectrograms, power spectral density percentile plots, 1/3 octave band levels, and generalised estimating equations to identify prominent soundscape contributors and investigate temporal patterns in their occurrence. The soundscape was found to be strongly influenced by wind, snapping shrimp, and vessel traffic, with the sounds of bridge traffic, waves, fish, machinery, dolphins, and precipitation also contributing to the acoustic environment. Furthermore, three of these sound sources (boats, waves, and fish) were found to vary at a range of temporal scales. These results take a vital step in characterising the acoustic habitat of this river system, highlighting the need to consider temporal patterns when assessing the composition of underwater soundscapes.